Safety and efficacy of transcatheter left atrial appendage closure using the Watchman device in Egyptian patients with nonvalvular atrial fibrillation - Hazem Khamis; Ahmed Ramzy; Neama Elmelegy; Khaled Elrabbat; Ahmed Masoud (The Egyptian Heart Journal, 2016)
Background: Atrial fibrillation (AF) is considered the major cause of stroke in the elderly. Alternative therapies to the anticoagulant therapy are warranted, particularly in patients who are ineligible or at high risk of bleeding. The left atrial appendage (LAA) is a prominent source of thrombi in nonvalvular AF, accounting for 90% of thrombi. As a result, surgical and transcatheter techniques have been explored to reduce the risk of stroke in patients with AF by occluding the LAA. Objectives: To assess the safety and efficacy of LAA closure in patients with nonvalvular atrial fibrillation (AF) ineligible for warfarin therapy. Methods: A prospective study that evaluated LAA closure with the Watchman device (Boston Scientific, Natick, MA; group A) in fifteen patients with nonvalvular AF and CHADS2 (congestive heart failure, hypertension, age ⩾75 years, diabetes mellitus, and prior stroke or transient ischemic attack) score ⩾1, who were considered ineligible for warfarin therapy. The primary efficacy endpoint was the combined events of ischemic/hemorrhagic stroke, systemic embolism and cardiovascular/unexplained death during a period of six months follow-up. Results: Successful closure of the LAA using the Watchman device was achieved in 15 patients (100%). The mean age was found to be 67.9 ± 9 years with 40% of them being males. No device or procedure related adverse events were detected. The mean CHADS2 score was 2.4 ± 0.8, while the mean CHA2DS2-VASC score was 4.4 ± 1.0. After a mean period of 8 ± 2 months of follow-up, no device dislodgement or device-related thrombi were documented. The all-cause stroke (ischemic and hemorrhagic) and systemic embolism were 0%. The device and procedure related mortality was found to be 0%. Only one patient died after 8 months of device implantation from pneumonia. Conclusion: LAA closure with the Watchman device can be safely performed, and may be a reasonable alternative to consider for patients at high risk for stroke but with contraindications to systemic oral anticoagulation or with high risk of bleeding.